Structuring Lis Curriculum for Online Teaching: a Proposed Study - Saravanan, T. (Journal of Information and Knowledge, 2014)
The label ’information society’ means different things to different people. For some, it ’signifies individuals’ access to information on a vast range of topics, delivered using a variety of different communication media, and the greater diversity of knowledge and experience that such new technologies permit. One can decide where one works and how one works. One can also decide with whom and when one socializes, by using e-mail and answering machines to filter communication and by using online shopping etc to avoid social contact. This paper encompasses an attempt for harnessing Online LIS curriculum.